2005
DOI: 10.1007/s00464-004-8930-x
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic versus total mesorectal laparoscopic resections of T2–N0 low rectal cancers after neoadjuvant treatment: a prospective randomized trial with a 3-years minimum follow-up period

Abstract: The findings show comparative results between the two study arms in terms of probability of failure and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 16 publications
4
54
0
4
Order By: Relevance
“…The only series on TEM following neoadjuvant chemoradiotherapy showed the procedure to be feasible with promising early results [66]. Again however, before definite conclusions can be drawn, larger, randomized studies have to be initiated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The only series on TEM following neoadjuvant chemoradiotherapy showed the procedure to be feasible with promising early results [66]. Again however, before definite conclusions can be drawn, larger, randomized studies have to be initiated.…”
Section: Discussionmentioning
confidence: 99%
“…If local control is improved by preoperative radiotherapy and preoperative chemoradiotherapy results in sterilizing lymph node metastases, local excision following preoperative chemoradiotherapy might be a logical step. One randomized controlled trial investigating this treatment strategy was performed [66]. Forty patients with histological proven adenocarcinomas, staged as uT2-N0-M0, G1/2, within 6 cm from the anal verge, were randomized to TEM or laparoscopic TME.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Local excision of advanced rectal cancers with curative intent remains a debatable issue. The review recommended that TEM only be used for palliative cases in T2-T3 tumors, nevertheless, researchers in several studies have described that TEM is safe and effective for patients with rectal carcinoma pT2 N0 low risk after neoadjuvant therapy and pT3 N0 low risk and complete response after neoadjuvant therapy who refused abdominal surgery [4,5,[9][10][11][12][13]22,26,[30][31][32]. Our experience has shown that neoadjuvant therapy followed by TEM to treat T2-3 N0 rectal cancer is well tolerated and effective.…”
Section: Discussionmentioning
confidence: 90%
“…TEM of more advanced rectal cancer remains a controversial issue. However TEM has recently become a more attractive option because of the regular use of neoadjuvant therapy at several centers [4,5,[8][9][10][11][12][13]. Still other indications have also been described: repair of high or supralevator fistulas, rectourethral fistulas and rectal prolapse, drainage of pelvic collections, impacted fecaloma and excision of extra rectal masses [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Postoperative chemoradiotherapy is a reasonable option for patients who were thought to have T1 lesions, but then on pathology, had either a higher stage lesion or unfavorable histology. 6 NCCN guidelines currently recommend abdominal surgery for these patients, but patients might decline this option for a number of reasons.…”
mentioning
confidence: 99%